2013
DOI: 10.1063/1.4798320
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids form strongly bound anions when substituted with superhalogen ligands

Abstract: The properties of AA-Y(-) anions (where AA = cysteine, aspartic acid, lysine; Y = BF3, PF5) were investigated at the ab initio Outer Valence Green's Function (OVGF)∕6-311++G(3df,3pd)∕∕MP2∕6-311++G(d,p) level of theory. It is shown that introducing a superhalogen-like substituent to an amino acid (i.e., Cys, Asp, and Lys) results in obtaining molecules that bind an excess electron relatively strongly. The electronic stabilities of such resulting daughter anions are predicted to be substantial (5.3-6.9 eV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Until recently, much of the research on super‐ and hyper‐halogens focused on inorganic constituents. This is because the electron affinities of organic molecules are rather small.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, much of the research on super‐ and hyper‐halogens focused on inorganic constituents. This is because the electron affinities of organic molecules are rather small.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in some cases, such superhalogen substituents were found to render the anionic states stable (in a sense that a compound which does not form electronically stable anionic states was demonstrated to become capable of excess electron binding when the superhalogen substituent was introduced). This idea was successfully verified on certain well-known molecules (i.e., aliphatic and aromatic hydrocarbons [25], natural amino acids [26]) that do not bind extra electron. The resulting anions turned out to be very stable with their electron binding energies in the 4-6 eV range.…”
Section: Introductionmentioning
confidence: 96%
“…11,12 Recent works reported by Skurski and co-workers have indicated that introducing a superhalogen-like substituent into organic molecules, e.g., hydrocarbon and amino acid, 16-18 would regulate these molecules electronic properties. [16][17][18] Therefore the electronic properties of the organic species could be regulated by superhalogens. That is to say, the organic molecules, of which the anionic forms are unstable, [10][11][12][20][21][22] will produce stable anions after introducing superhalogen- 55 like substituent.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Albeit the F, Cl, and CN species are considered relatively effective oxidizing agents (due to their large electron affinities spanning the 3.40-3.90 eV range) [13][14][15] the resulting C 2 H 3 X, C 2 H 5 X, and C 6 H 5 X molecules (X = F, Cl, and CN) do not bind an excess electron to form electronically stable anions. 11,12 Recent studies reported by Skurski and co-workers have indicated that introducing a superhalogen-like substituent into organic molecules, e.g., hydrocarbons and amino acids, [16][17][18] would regulate the electronic properties of these molecules. These composite structures, 19 generated from the combination of organic molecules of small or even negative VDE with superhalogens, possess VDE values apparently higher than their organic parents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation